Effect of antenatal administration of magnesium sulphate and milking of umbilical cord during delivery on the incidence of intraventricular haemorrhage in preterm infants - Tom, Stephy Maria; Manoj, V. C. (International Journal of Contemporary Pediatrics, 2018)
Background: Intraventricular hemorrhage (IVH) is commonly seen in preterm infants. The aim of this study was to look at the effect of antenatal magnesium sulphate administration and milking of umbilical cord during delivery in the incidence of IVH in preterm infants. Methods: A randomized controlled study was conducted in the year 2015 on 80 preterm infants born less than 33 weeks of gestation during the study period. Magnesium sulphate was administrated to 25 pregnant women who were at imminent risk for delivery. Fourteen infants underwent milking of umbilical cord. The primary outcome was IVH detected in cranial ultrasound of day 28. Results: The primary outcome showed only 1 infant who received magnesium sulphate developed IVH, whereas 3 infants with no intervention done developed IVH. None of the preterm infants who had undergone milking of umbilical cord developed IVH. Conclusions: It was found that both antenatal administration of magnesium sulphate and milking of umbilical cord during delivery in preterm infants resulted in a significant reduction in the incidence of IVH. Further studies using more number of samples are required to understand the role of the interventions for long-term implications.